Seawater/C-cup: Fishy Trans Embodiments and Geographies of Sex Work in Newfoundland - Jefferies, Daze (Imaginations, 2020)
In this work of autoethnographic research-creation, I think with my augmented breasts—beyond the medical archive and away from the clinic—as an embodied inquiry into trans geographies of sex work in the island world of Ktaqamkuk/Newfoundland, Canada. Employing the felt knowledges of my breasts in visuals and poetics, I illustrate fishy entanglements shared between my sex work and breast augmentation that have reframed my social and sexual embodiment. Engaging with my breasts as a contact zone of embodied dis/pleasure, economic promise, and social violence, I suggest that paying creative attention to trans women’s breasts might reimage notions of trans sex-working desire.